Integrating Continuous Professional Development into Human Resource Management Systems in Public Education: A Case Study of SMA Negeri 1 Besuki Situbondo - Arifin, Samsul; Efendi, Erfan; Rahman, Zainor; Abdussyakir Z, Muhammad; Faifatur R, M. Kurma Nur (Journal of Quality Assurance in Islamic Education (JQAIE), 2025)
This study explores the integration of Continuous Professional Development (CPD) into the Human Resource Management (HRM) system in the context of public education at SMA Negeri 1 Besuki Situbondo. The main issue addressed in this study is the separation of teacher development programs from the school performance management system. The purpose of this study is to identify effective strategies for integrating CPD into HRM practices to improve teacher professionalism and strengthen institutional accountability. A qualitative case study approach was used in this study. Data were obtained through in-depth interviews, observations, and document analysis involving teachers, principals, and HR staff. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldaña through the stages of data condensation, data display, and conclusion drawing/verification. The results showed that integrating CPD into HRM shifted the school management paradigm from administrative compliance to competency-based development. The principal’s transformational leadership was a key factor in integrating training, performance evaluation, and career development within a cohesive framework. As a result, teachers experienced improvements in pedagogical competence, digital literacy, and learning innovation. The CPD–HRM integration model at SMA Negeri 1 Besuki Situbondo can be replicated to strengthen the human resource system in public education and build institutional performance.